2017
DOI: 10.1155/2017/1928795
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Tract Viral Infections and Coinfections Identified by Anyplex™ II RV16 Detection Kit in Pediatric Patients at a Riyadh Tertiary Care Hospital

Abstract: Respiratory infections are caused by an array of viruses, and limited information is available about viral coexistence, comparative symptoms, and the burden of illness. This retrospective cohort study aimed to determine the etiological agents responsible for respiratory tract infections by Anyplex II RV16 detection kit (RV16, Seegene), involving 2266 pediatric patients with respiratory infections admitted to the Department of Pediatrics at King Abdul-Aziz Medical City, Ministry of National Guard, Riyadh, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…Other investigations from regions of Saudi Arabia reported detection of various respiratory viruses like influenza A and B, parainfluenza 1, 2 and 3 enteroviruses and adenovirus along with RSV in the clinical samples [32,35,38,39,45]. A recent study reported the multiple viral infection with the RSVA (6.7%) and RSVB (7.8%) [44].…”
Section: Co-infection With Other Respiratory Virusesmentioning
confidence: 95%
See 4 more Smart Citations
“…Other investigations from regions of Saudi Arabia reported detection of various respiratory viruses like influenza A and B, parainfluenza 1, 2 and 3 enteroviruses and adenovirus along with RSV in the clinical samples [32,35,38,39,45]. A recent study reported the multiple viral infection with the RSVA (6.7%) and RSVB (7.8%) [44].…”
Section: Co-infection With Other Respiratory Virusesmentioning
confidence: 95%
“…A recent study conducted in Riyadh analysed 2266 paediatric patient NPAs/swabs with real-time PCR. The maximum RSV cases (29%) were reported in winter season of 2014-15 [44]. The prevalence of RSV ranged between 0.2% to 54% with an average of 22.8% (Figure 3).…”
Section: Prevalence Of Rsvmentioning
confidence: 97%
See 3 more Smart Citations